2021
DOI: 10.22541/au.163332477.72689073/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating performance of soil water movement and groundwater recharge in an irrigated agricultural area of Yinchuan Plain, China

Abstract: Surface irrigation has been predominantly used for field crops in agriculture area to boost agricultural yields and outputs, however, this may also raise groundwater tables, salinize soils and reduce water quality due to poor irrigation management. Therefore, it is essential for requiring a better understanding of the hydrologic mechanisms related to soil water fluxes (e.g., evaporation, transpiration, infiltration, deep percolation and groundwater capillary rise) by surface irrigation. This study investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…After years of development, HYDRUS-1D has seen widespread use and can effectively model variations in soil moisture, temperature, and solute concentrations due to agricultural irrigation and fertilization. The vertical transport of soil moisture in both saturated and unsaturated media is governed by the modified Richards equation and the van Genuchten model [27], as detailed in Equations ( 5)- (8):…”
Section: Hydrus-1d Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…After years of development, HYDRUS-1D has seen widespread use and can effectively model variations in soil moisture, temperature, and solute concentrations due to agricultural irrigation and fertilization. The vertical transport of soil moisture in both saturated and unsaturated media is governed by the modified Richards equation and the van Genuchten model [27], as detailed in Equations ( 5)- (8):…”
Section: Hydrus-1d Modelmentioning
confidence: 99%
“…The water cycle serves as the crucial link connecting various terrestrial systems, such as the hydrosphere, atmosphere, lithosphere, and biosphere [2] Hydrological models [3][4][5][6] have proven to be effective tools for exploring the complex mechanisms of water cycling in irrigation districts and are indispensable in research related to water resource management and the impact of human productive activities on the water cycle [7]. Numerous scholars have carried out both experimental and numerical simulation studies on the water cycle in irrigation areas [8][9][10]; however, these investigations tend to be expensive and time-consuming, and the outcomes are often specific to each study. The advent of the hydraulic model HEC-RAS [11] and agricultural hydrological models such as HYDRUS [12], SWAT [13], and SWAP [14] has provided deeper insights into the dynamics of soil moisture and the behavior of water cycles within irrigation districts [15].…”
Section: Introductionmentioning
confidence: 99%
“…They found that groundwater was recharged by rainfall, the Yellow River, and irrigation. Yin [20] used the resistivity sounding method to explore the groundwater recharge conditions at a depth of 300 m in the Yinchuan Plain based on hydrogeological survey results from previous studies. The results showed that the source of groundwater recharge of the proluvial fan in the Helan Mountains is atmospheric precipitation and bedrock fissure water.…”
Section: Introductionmentioning
confidence: 99%